Effect of etomidate on systemic and regional cerebral perfusion in neonates and infants with congenital heart disease: A prospective observational study. Issue 9 (6th August 2020) - Dennhardt, Nils; Elfgen‐Schiffner, Frederike‐Debora; Keil, Oliver; Beck, Christiane E.; Heiderich, Sebastian; Sümpelmann, Robert; Nickel, Katja
Abstract: Background: Neonates and infants with congenital heart disease undergoing general anesthesia have an increased risk for critical cardiovascular events. Etomidate produces very minimal changes in hemodynamic parameters in older children with congenital heart disease. There is a lack of studies evaluating the effect of etomidate on systemic and regional cerebral perfusion in neonates and infants with congenital heart disease. Aim: The aim of this prospective observational study was to evaluate the effect of etomidate on systemic and regional cerebral perfusion in neonates and infants with congenital heart disease. Methods: In fifty infants aged 0‐11 months (24% neonates n = 12) with congenital heart disease, mean arterial blood pressure, cardiac index using electrical cardiometry, and regional cerebral oxygen saturation using near‐infrared spectroscopy were measured at baseline and 1, 3, 5, and 10 minutes after induction by 0.4 mg kg −1 etomidate. Hypotension was defined as a mean arterial blood pressure under 35 mm Hg and cerebral desaturation as a regional cerebral oxygen saturation of less than 80% of baseline. Results: Mean arterial blood pressure, cardiac index, and regional cerebral oxygen saturation remained stable above the predefined limits. Mean arterial blood pressure decreased slightly within a physiological range after 3 minutes ( P  = .005, 95% CI:‐5.9 to −1.0). No significant change in cardiac index could be observed. Conclusion: Etomidate 0.4mg kg −1 does not impair systemic or regional cerebral perfusion in neonates or infants with congenital heart disease.